DIMENSIONS OF ISLAMIC PHILOSOPHY IN OBSERVING RELIGIOUS MODERATION - Vick Ainun Haq; Achmad Khudori Soleh; Asti Amelia (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2023)
ABSTRACT One of the problems that happens regarding religious moderation is that many people do not claim a particular religion, whether or not religious moderation only applies to individuals or groups who have a religion. The role of Islamic Philosophy seems to be urged to solve the problem. To explore the variety of Islamic philosophical thoughts led this article to discuss the thoughts of Suhrawardi, the founder of Isyraqi philosophy. This article aimed to analyze the concept of Isyraqi philosophy related to the esoteric concept of religious pluralism and its relationship to human tolerance in the discourse of religious moderation. This research applied a literature review, collecting information sourced from books and journal articles, especially about Suhrawardi’s thoughts as the primary source and relevant studies as the secondary source. The results of the research showed that; (1) Allah SWT is the main source for the creation of knowledge, religions and beliefs (2) Isyraqi philosophy acknowledges the esoteric nature of pluralism as the basis of ethical concepts (3) Tolerance is based on the awareness to decline every single fanaticism towards reality. Thus, because of the implications of the philosophical thinking above, religious moderation should cover all levels of society, both the believers and non-believers. ABSTRAK Pada faktanya masih banyak masyarakat yang tidak mengklaim agama tertentu, disinilah masalah moderasi beragama, apakah moderasi beragama hanya berlaku untuk seseorang atau kalangan yang memiliki agama? Peran Filsafat Islam seakan didesak untuk menjawab pertanyaan tersebut. Menelusuri ragam pemikiran Filsafat Islam mengantarkan artikel ini untuk mendiskusikan pemikiran Suhrawardi, sosok pencetus Filsafat Isyraqi. Artikel ini bertujuan menganalisis konsep Filsafat Isyraqi terkait konsep esoteris pluralisme agama dan kaitannya dengan toleransi umat manusia dalam wacana moderasi beragama. Proses penelitian ini menggunakan tinjauan pustaka, pengumpulan informasi bersumber dari buku maupun artikel jurnal, terutama tentang pemikiran Suhrawardi sebagai sumber primer dan yang relevan dengan tema-tema terkait sebagai sumber sekunder. Hasil dari penelitian ini menunjukan bahwa; (1) Allah Swt merupakan sumber utama atas terciptanya ilmu, agama-agama dan keyakinan (2) Filsafat Isyraqi mengakui hakikat esoteris pluralis sebagai dasar konsep etika (3) Toleransi didasari dengan kesadaran menolak fanatisme tunggal terhadap realitas. Dengan demikian sebabagai implikasi pemikiran filsafat di atas maka selayaknya Moderasi Beragama harus mencakup seluruh lapisan masyarakat baik bagi penganut agama maupun tidak (penganut kepercayaan)